Augmenting the Structures in a Swirling Flame via Diffusive Injection. (13th August 2014) - Lewis, Jonathan; Valera-Medina, Agustin; Marsh, Richard; Morris, Steven
Abstract : Small scale experimentation using particle image velocimetry investigated the effect of the diffusive injection of methane, air, and carbon dioxide on the coherent structures in a swirling flame. The interaction between the high momentum flow region (HMFR) and central recirculation zone (CRZ) of the flame is a potential cause of combustion induced vortex breakdown (CIVB) and occurs when the HMFR squeezes the CRZ, resulting in upstream propagation. The diffusive introduction of methane or carbon dioxide through a central injector increased the size and velocity of the CRZ relative to the HMFR whilst maintaining flame stability, reducing the likelihood of CIVB occurring. The diffusive injection of air had an opposing effect, reducing the size and velocity of the CRZ prior to eradicating it completely. This would also prevent combustion induced vortex breakdown CIVB occurring as a CRZ is fundamental to the process; however, without recirculation it would create an inherently unstable flame.